HYDROGRAPHY OF THE COCHIN HARBOUR - PILLAI, A. G GOPALAKRISHNA (Fishery Technology, 2017)
The hydrography of the Cochin harbour is studied with reference to air temperature, dissolved oxygen, salinity and pH. The analysis of the data shows unique hydrographical characteristics which are influenced by the monsoon rains. The uniqueness lies mainly in the fluctuations of salinity which registers as low as 0.6 /aÂ° during monsoon period to near sea conditions (29.4 /0.) during the summer period. The dissolved oxygen, temperature and pH also showed fluctuations corresponding to seasons.